Czy szkoła uczy mówienia? O ustnych wypowiedziach gimnazjalistów - Tabisz, Anna (Polonistyka. Innowacje, 2015)
The article consists of two sections. In the first part of the article the author discusses the aim and course of the study on the level of mastery by junior high school students their ability to create a coherent monologue, oral statements and the author presents results that indicate that the students do not succeed satisfactory in speaking out. The most difficult point for the tested students was, as it turned out, talking in a comprehensive manner and building consistent and orderly expressions. Interestingly, rhetorical aspect was made slightly better. In the second part of the article the author is trying to identify the reasons for poor control of speaking (limited to the factors of school). These include the abuse on Polish language lessons, the usage of heuristic methods, as well as the absence of tasks in textbooks for teaching Polish aiding the improvement of speaking skills.